DIGITAL GOVERNANCE AND PUBLIC SERVICE INNOVATION: CHALLENGES FOR CONTEMPORARY PUBLIC ADMINISTRATION - Murat Arslan; Zeynep Toprak; Cemil Kaya; Eka Anjani Sapitri (Yayasan Adra Karima Hubbi, 2026)
Digital governance has become a central strategy in contemporary public administration, driven by rapid technological advancements and increasing demands for efficient, transparent, and citizen-centered services. The integration of digital technologies promises to transform public service delivery; however, the extent to which these transformations result in meaningful innovation remains contested. The study aims to examine how digital governance influences public service innovation and to identify the institutional and organizational challenges that shape its effectiveness. A mixed-methods research design was employed, combining survey data from 120 public sector professionals with qualitative analysis of interviews and policy documents. Quantitative analysis was conducted using descriptive and inferential statistics, while qualitative data were analyzed through thematic coding to capture contextual dynamics. The findings reveal that digital governance significantly improves operational efficiency but has limited impact on citizen engagement and participatory outcomes. Evidence indicates that organizational capacity, leadership, and institutional culture play critical roles in mediating innovation processes, often constraining the transformative potential of digital technologies. The study concludes that digital governance should be understood as a socio-technical process requiring alignment between technology, institutions, and citizen needs, offering important implications for policy development and administrative reform.